1991
DOI: 10.1152/ajpcell.1991.260.6.c1158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epidermal growth factor on magnesium homeostasis in BC3H1 myocytes

Abstract: The acute effects of epidermal growth factor (EGF) on Mg2+ homeostasis were studied in differentiated BC3H1 myocytes. EGF produced a 48-fold stimulation of [3H]thymidine incorporation into quiescent serum-starved cells in the presence of Mg2+, whereas insulin had no effect on [3H]thymidine incorporation. The dose dependence of EGF-stimulated [3H]thymidine incorporation was similar to that of EGF stimulation of 28Mg2+ uptake. In cells loaded with the Mg(2+)-sensitive fluorescent indicator, Mag-fura-2, intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 30 publications
5
23
1
Order By: Relevance
“…It suggests that thymidine kinase is saturated for MgATP 2Ϫ , even in quiescent cells, whereas uridine kinase is not saturated in such cells and could be activated by any increase in Mg 2ϩ induced by growth factors. That Mg 2ϩ , rather than ATP 4Ϫ , is the regulator of uridine trapping is consistent with the failure of ATP to increase in growth-stimulated cells (17,(20)(21)(22), whereas total Mg 2ϩ (23,24) and free Mg 2ϩ (25,26) do increase in a sustained manner after treatment with growth factors.There are, however, some problems in a simple interpretation of the published effects on uridine uptake͞trapping caused by varying the Mg 2ϩ concentration in cells. To achieve a wide range of Mg 2ϩ concentrations in cells, the Ca 2ϩ concentration of the medium was reduced to increase the permeability of the cells to Mg 2ϩ (16,17,27).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…It suggests that thymidine kinase is saturated for MgATP 2Ϫ , even in quiescent cells, whereas uridine kinase is not saturated in such cells and could be activated by any increase in Mg 2ϩ induced by growth factors. That Mg 2ϩ , rather than ATP 4Ϫ , is the regulator of uridine trapping is consistent with the failure of ATP to increase in growth-stimulated cells (17,(20)(21)(22), whereas total Mg 2ϩ (23,24) and free Mg 2ϩ (25,26) do increase in a sustained manner after treatment with growth factors.There are, however, some problems in a simple interpretation of the published effects on uridine uptake͞trapping caused by varying the Mg 2ϩ concentration in cells. To achieve a wide range of Mg 2ϩ concentrations in cells, the Ca 2ϩ concentration of the medium was reduced to increase the permeability of the cells to Mg 2ϩ (16,17,27).…”
supporting
confidence: 58%
“…It suggests that thymidine kinase is saturated for MgATP 2Ϫ , even in quiescent cells, whereas uridine kinase is not saturated in such cells and could be activated by any increase in Mg 2ϩ induced by growth factors. That Mg 2ϩ , rather than ATP 4Ϫ , is the regulator of uridine trapping is consistent with the failure of ATP to increase in growth-stimulated cells (17,(20)(21)(22), whereas total Mg 2ϩ (23,24) and free Mg 2ϩ (25,26) do increase in a sustained manner after treatment with growth factors.…”
supporting
confidence: 58%
“…Initial studies in cultured cells showed that applying insulin induced 20% higher intracellular Mg 2ϩ concentrations after 16 h (445). Later studies with EGF using the fluorescent probe mag-fura 2 showed an impressive fourfold increase of intracellular Mg 2ϩ from 0.3 to 1.4 mM after 20 min of epidermal growth factor (EGF) stimulation (199). The authors state that a rise in Mg 2ϩ precedes DNA synthesis, but coincides with and thus may contribute to increases in protein synthesis.…”
Section: E Cell Proliferationmentioning
confidence: 99%
“…Thus, pervanadate action on such a channel is a strong possibility. Indeed, in a recent report, Grubbs (1991) found that epidermal growth factor (EGF) increases both Mg2' uptake and intracellular free Mg2+ in BC,H1 myocytes, but does not alter Mg2+ efflux. In those cells, the dose-response curves for EGF stimulation of thymidine incorporation and Mg2+ uptake were similar, suggesting a relationship between increased Mg2' uptake and mitogenesis.…”
Section: Mg2+ As a Second Messengermentioning
confidence: 99%